Growth Performance of Sargassum cristaefolium in Gerupuk Bay, Central Lombok - Nunik Cokrowati; Eka Sunarwidhi; Baiq Raihanun; Ni Kadek Puji Astuti; Muhammad Heri Hariadi; Muhamad Jumat; Dimas Putra Perdana; Bq. Tri Khairina ilhami; Jayusri Jayusri; Dinda Cristasya Waang; Hasriaton Padmi; Nanda Kurniawan (Jurnal Media Akuatika, 2024)
Sargassum cristaefolium seaweed is a seaweed that has a dominant polysaccharide content including alginate, laminarin, and fucoidan which is usually used in the food, textile, pharmaceutical, agricultural, and cosmetic industries. Many of benefits that S. cristaefolium has, it causes the export volume of seaweed to increase so that indirect production also increases. However, S. cristafolium has not been cultivated on a mass basis in NTB, especially on the island of Lombok. The potential of S. cristaefolium seaweed which is supported by the aquatic environment of Gerupuk Bay which is suitable for cultivation. But at the level of cultivators, what is still a problem is the use of early seaweed seeds. The purpose of this study was to analyze the differences in the growth of S. cristaefolium cultivated with different seed weights. The method used is an experimental method using a Completely Randomized Design (CRD). The treatments in this study consisted of 5 treatments and 4 replications, namely P1 (seedling weight 100 g), P2 (seedling weight 75 g), P3 (seedling weight 50 g), P4 (seedling weight 25 g), P5 (seedling weight 125 g). Data were analyzed using Analysis of variance (ANOVA) and then continued with Duncan's test with a 95% confidence level. The best absolute growth research results were in the P1 treatment (seed weight 100 g) which was 91.25 g. While the best specific growth rate was in treatment P4 (seedling weight 25 g) with a value of 7.84%. This study concludes that different seed weight affects the growth of S. cristaefolium seaweed.